TINJUAN YURUDIS PENERAPAN KEBIJAKAN ANTI SLAP DI INDONESIA (ANALISA PUTUSAN 14. PID.SUS/2024/ PN JPA) - Missleini Missleini; Nynda Fatmawati O (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The state's obligation to protect activists is a crucial aspect of human rights enforcement and democracy. Despite existing legal frameworks, both domestic and international, many activists still face significant threats in practice. The decision in Jepara District Court Case No. 14 Pid.Sus/2024/PN Jpa illustrates challenges in safeguarding freedom of expression, particularly on environmental issues. This case raises concerns about the inadequate implementation of anti-SLAPP policies, which aim to protect public participation. The ruling risks suppressing freedom of speech and creating a chilling effect on environmental activists. Protecting activists through legal reforms and consistent policy implementation is essential to fostering democracy, social justice, and public engagement in critical discussions.